- Pengolahan Citra Digital Pada Buah Nanas Menggunakan Metode Linear Discriminant Analisys (LDA): - - ninosari, Devina Ninosari devina; Mardiana, Yessi (Universitas Lembah Dempo, 2022)
Pineapple is a fruit commodity that is superior to Indonesia. This is because pineapple is afruit that has the highest export volume in Indonesia. To obtain pineapples with perfectripeness, they are generally selected manually, this becomes inefficient if large quantities ofpineapples are selected. So, in this study an image processing system will be developed thatcan classify the ripeness of pineapple fruit based on its image. In this study, the color featureextraction used is feature extraction based on hue and saturation values. Color featureextraction with hue and saturation is used to obtain various information from the colors inthe image so as to facilitate the identification process. Furthermore, Linear DiscriminateAnalysis will get the optimal projection to be able to enter spaces with smaller dimensions bydoing pattern recognitionwhich can be separated so that they can be grouped based on the boundary line obtainedfrom the linear equation. Based on the results of the accuracy test, the accuracy levelreaches 83%, which is included in the good category